How Has the Digital Transformation Affected the Organization and Operation of a Business - Chenyu Xiao (Law and Economy, 2023)
With the continuous advancement of information technology (IT), the information era has arrived, whereby digital technologies “has transformed many aspects of everyday life[1]” and work, with business being one of the primary aspects as well. The digital transformations, which “take two primary shapes: digitalization and datafication,[2]” have fundamentally altered the development model of modern businesses, bringing about revolutionary enhancements to business organization and operation. The use of advanced technologies such as Artificial Intelligence (AI) has considerably boosted the efficiency of corporate management and decision-making processes. Besides, the use of telecommunication tools has promoted “the widespread shift to distributed work,[3]” making it significantly easier to conduct business across diverse jurisdictions. However, the adoption of information technologies in enterprises can also be detrimental. For example, incorporating AI into the decision-making processes within the boardroom may lead to slackness and negligence of the directors. On this basis, this essay will introduce the key characteristics of digital transformation and its impact on corporate governance. Furthermore, with respect to the drawbacks of sandbox, this essay proposed a disclosure-based regulatory framework.